Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.20944/preprints202106.0255.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Preparedness and Perceived Safety in 138 Nursing Homes in Southern Portugal: A Cross-sectional Survey-based Study in the Initial Phases of the Pandemic

Abstract: (1) Background: Nursing homes’ preparedness in managing a public health crisis has been fragile, with effects on safety culture. The objective of this study was to assess nursing homes’ COVID-19 preparedness in Southern Portugal, including personnel’s work experiences during the pandemic. (2) Methods: We used a COVID-19 preparedness checklist to be completed by management teams, followed by follow-up calls to nursing homes. Thereafter, a survey to personnel was applied. Data analy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…This single-site working policy, along with high absenteeism and pre-existing staffing shortages, compounded workforce management issues ( Dykgraaf et al., 2021 ; van Tol et al., 2021 ). Therefore, several organizations had to employ temporary staff, non-healthcare nursing home staff, or army medical staff ( Fernandes et al., 2021 ; Gray et al., 2021 ; Jones et al., 2021 ). Despite these efforts to boost staff, many studies reported increased workloads and fear of becoming infected or spreading the virus, as well as a higher emotional burden among nursing home staff ( Gray et al., 2021 ; Hendricksen et al., 2022 ; van Dijk et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This single-site working policy, along with high absenteeism and pre-existing staffing shortages, compounded workforce management issues ( Dykgraaf et al., 2021 ; van Tol et al., 2021 ). Therefore, several organizations had to employ temporary staff, non-healthcare nursing home staff, or army medical staff ( Fernandes et al., 2021 ; Gray et al., 2021 ; Jones et al., 2021 ). Despite these efforts to boost staff, many studies reported increased workloads and fear of becoming infected or spreading the virus, as well as a higher emotional burden among nursing home staff ( Gray et al., 2021 ; Hendricksen et al., 2022 ; van Dijk et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of several landmark reports, such as To Err is Human (Donaldson, Corrigan and Kohn, 2000 [4]), patient safety has become widely recognized as an ethical, economic, and public health issue warranting research and improvement initiatives. More recently, patient safety culture (PSC) has been increasingly recognized as a fundamental component in creating and maintaining safe health care systems-a strategy for improving patient safety (de Bienassis et al, 2020 [5]; Weaver et al, 2013[6]).…”
mentioning
confidence: 99%
“…This format of data presentation is routinely used in OECD publications, such as Health at a Glance (OECD, 2019 [42]). Figure 2.9 shows the change in country level average scores between 2021-2017 and 2016-2012 on the domain of "Frequency of Events Reported" 4 . For countries with available data for each of these time periods, the Netherlands and the United States saw improvements, while France and Israel saw declines over the same time period.…”
mentioning
confidence: 99%